Japanese families in diaspora: child-rearing practices: a comparative study of 'stayers' and 'sojourners' in Western Australia. - Becker, Anne (Curtin University, 2002)
This thesis investigates and analyses the child-rearing patterns of two groups of Japanese parents living in Perth, Western Australia. The first group, the 'Stayers have migrated to Australia as a couple with the intention of making Australia their home and occasionally visiting Japan with their children. The second group, the Sojourners' are in Australia for a fixed period of time, generally 4-5 years, as a result of the company requirements expected of the husband/father. Their time in Australia is an interlude, an experience, an opportunity for the whole family.The research compares a number of case studies of families in both groups. In depth interviews following detailed questionnaires provide the data about the child-rearing practices as expressed by mothers and fathers in the two groups. Parental expectation of children's private and public behaviour, as well as their relevance to gender and age are explored.The findings from the survey suggested that the qualities held to be the most important for the Stayer group were those qualities that would be useful for their children to be successful in Australia. Qualities such as independence, assertiveness and using initiative were rated as being more desirable to develop for the children in the Stayer group than those children in the Sojourner group. Some Stayer families with older children had socialised their children to operate successfully in both cultures. The findings also suggested that the qualities held to be important for the Sojourner group were consistent with the qualities that the Japanese view as being valued for Japanese in Japan.